2011
DOI: 10.1364/oe.19.025465
|View full text |Cite
|
Sign up to set email alerts
|

Ring-resonator-integrated tunable external cavity laser employing EAM and SOA

Abstract: We propose and demonstrate a tunable external cavity laser (ECL) composed of a polymer Bragg reflector (PBR) and integrated gain chip with gain, a ring resonator, an electro-absorption modulator (EAM), and a semiconductor optical amplifier (SOA). The cavity of the laser is composed of the PBR, gain, and ring resonator. The ring resonator reflects the predetermined wavelengths into the gain region and transmits the output signal into integrated devices such as the EAM and SOA. The output wavelength of the tunab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, the coupling loss between the waveguide and the gain chip is still high, which limits any increase in the laser output power. Currently, the University of California, Santa Barbara (UCSB) in the USA [93], NEC Corporation in Japan [41], Institute of Semiconductors, Chinese Academy of Sciences [42], Columbia University in the USA [43], University of Tampere in Finland [19], Dublin City University in Ireland [40,44], among other institutions [94][95][96] have conducted in-depth research on MRR-ECDLs.…”
Section: Waveguide-type Ecdlmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the coupling loss between the waveguide and the gain chip is still high, which limits any increase in the laser output power. Currently, the University of California, Santa Barbara (UCSB) in the USA [93], NEC Corporation in Japan [41], Institute of Semiconductors, Chinese Academy of Sciences [42], Columbia University in the USA [43], University of Tampere in Finland [19], Dublin City University in Ireland [40,44], among other institutions [94][95][96] have conducted in-depth research on MRR-ECDLs.…”
Section: Waveguide-type Ecdlmentioning
confidence: 99%
“…Thus, it is typically mixed and integrated with other components to obtain the tuning function required to achieve the tuning wavelength. In 2011, research on ECDLs based on polymer Bragg reflectors (PBRs) and single MRRs was reported by the Korea Electronics and Telecommunications Research Institute [95]. The resonant cavity of the laser is composed of a PBR, gain chip, and single MRR.…”
Section: Waveguide-type Ecdlmentioning
confidence: 99%
“…On the other hand, hybrid integration between photonics chips and semiconductor lasers provides an ideal method to fabricated ECLs. These hybrid integration ECLs have been investigated based on different materials, such as III-V [3], silicon [10][11][12], silica [6], SiN [13], and polymers [14][15][16]. Compared with other materials, silica planar lightwave circuits (PLCs) are attractive for ECLs owing to its high mechanical strength, high thermal stability, low loss, and almost the same core geometry with fiber cores, which is suitable for an optical communication system.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the microring resonators (MRRs) with compact sizes and ultrahigh-Q factors show great potential in lasers [10][11][12][13][14]20], sensors [21][22][23][24], and filters [25][26][27][28]. Compared with basic MRRs, the racetrack MRRs using lateral coupling, increase the coupling gap size and the fabrication tolerance.…”
Section: Introductionmentioning
confidence: 99%